2021
DOI: 10.3892/etm.2021.9942
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA TTTY15 alleviates ischemia/reperfusion‑induced inflammation and apoptosis of PC12 cells by targeting miR‑766‑5p

Abstract: The pathogenesis of ischemic stroke is extremely complex and has a significant impact on the quality of life of the patients. Accumulating studies have reported that long non-coding RNAs (lncRNAs) may be associated with the progression of ischemic stroke. However, the role and underlying mechanism of action of the lncRNA testis-specific transcript Y-linked 15 (TTTY15) in ischemic stroke remains unknown. The present study analyzed the expression levels of TTTY15 in PC12 cells injured by oxygen-glucose deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This study identified a potential downstream miRNA (miR-766) of circPTK2 and found that miR-766 was down-expressed in both models of septic ALI, but circPTK2 depletion restored miR-766 levels. miR-766 has been recognized to suppress skin inflammation 35 and attenuate ischemia/perfusion injury-induced cellular inflammation and apoptosis 36 . The paper demonstrated that miR-766 overexpression mitigated the effects of circPTK2 overexpression on cytotoxicity, eATP levels, inflammation, and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified a potential downstream miRNA (miR-766) of circPTK2 and found that miR-766 was down-expressed in both models of septic ALI, but circPTK2 depletion restored miR-766 levels. miR-766 has been recognized to suppress skin inflammation 35 and attenuate ischemia/perfusion injury-induced cellular inflammation and apoptosis 36 . The paper demonstrated that miR-766 overexpression mitigated the effects of circPTK2 overexpression on cytotoxicity, eATP levels, inflammation, and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a newly discovered lncRNA, TTTY15 has been shown to play a crucial role in cardiovascular diseases. For instance, Zheng et al [ 34 ], Chen et al [ 35 ], Huang et al [ 36 ], Hao et al [ 37 ], and Zhang et al [ 38 ] have reported that TTTY15 silencing can sponge miR-186-5p, miR-374a-5p, miR-455-5p, miR-766-5p, and let-7i-5p to mitigate hypoxia-induced vascular endothelial cell injury. Moreover, dysregulation of TTTY15 has been observed in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, according to Orr's observation (Orr, 1993), the testis-specific expression of Xt-mir seems to be controlled by the gene on the Y chromosome. Although there is no miRNA on the Y chromosome (Ji et al, 2016), Long noncoding RNA (lncRNA) was present, and it was shown that KO of Y-linked lncRNA upregulated miRNA and suppressed apoptosis (Hao et al, 2021). LncRNA, which is non-coding RNA with a length of 200 bases or more, exists widely in diverse species including viruses, prokaryotes, and eukaryotes, and is often expressed organ-specifically in animals, especially in the testis (Hong et al, 2018).…”
Section: Wolbachia and The Last Bossmentioning
confidence: 99%